2020
DOI: 10.1016/j.indcrop.2020.112867
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sustainable bioprocess based on green technologies for xylitol production from corn cob

Abstract: In this work, a sustainable and environmental friendly strategy for the biotechnological production of xylitol was proposed and optimized. For this purpose, corn cob was hydrothermally pretreated at high solid loadings (25%) for an efficient solubilization of xylan in hemicellulose derived compounds, xylooligosaccharides and xylose. Xylose enriched streams were obtained from the enzymatic saccharification of the whole slurry (solid and liquid fraction) resulting from the autohydrolysis pretreatment. The xylito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Our data showed that although DX7 had much stronger XR activity than X3, xylitol production capacity of X3 was much greater than that of DX7 in WXML fermentation. We suspect the cause is based on their different metabolic characteristics, particularly the accumulation of acetate (Figs 4 and 5), which is toxic to yeasts (Semchyshyn et al ., 2011; Orlandi et al ., 2013) and shows negative effect on the yeast‐based xylitol production process (Baptista et al ., 2020). The acetate produced by DX7 kept accumulating after 36 h of fermentation, while the acetate produced by X3 did not accumulate and actually decreased after 36 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showed that although DX7 had much stronger XR activity than X3, xylitol production capacity of X3 was much greater than that of DX7 in WXML fermentation. We suspect the cause is based on their different metabolic characteristics, particularly the accumulation of acetate (Figs 4 and 5), which is toxic to yeasts (Semchyshyn et al ., 2011; Orlandi et al ., 2013) and shows negative effect on the yeast‐based xylitol production process (Baptista et al ., 2020). The acetate produced by DX7 kept accumulating after 36 h of fermentation, while the acetate produced by X3 did not accumulate and actually decreased after 36 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…glucose or glycerol) because they are cheaper than xylose is also a common strategy to achieve high yields of xylitol with low production cost (Dasgupta et al ., 2017; Hua et al ., 2019; Park et al ., 2019; Xu et al ., 2019). Recently, the SSF process was also used in xylitol production from corn cob whole slurry (Baptista et al ., 2018; Baptista et al ., 2020). The high yield was gotten, while the final xylitol titer was limited by the xylose concentration in the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges of using sugarcane hydrolysate in whole-cell fermentation resides in the inhibitory nature of several pretreatment by-products. While such hemicellulosic feedstock has been tested for xylitol production using yeast Candida guilliermondii [53,54], approaches using recombinant S. cerevisiae have been limited to either corn cob [15,17,18,55], rice straw or woody biomass [16,56] as natural xylose sources. Using sugarcane biomass to produce high added-value chemicals with S. cerevisiae is a prospect for future biorefineries [57], and our experiments join this discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the biomass is treated at high pressure and temperature of around 200 • C due to which the acetyl groups in the hemicellulose get hydrolyzed to release acids that break bonds between the carbohydrates and lignin. Baptista et al (2018Baptista et al ( , 2020) have used the auto-hydrolysis method to pretreat corncob and have reported the highest titer of xylitol production using recombinant Saccharomyces cerevisiae.…”
Section: Pretreatment and Hydrolysismentioning
confidence: 99%